Silencing monologic teaching in ELICOS - Ekici, Gail (Universitas Ahmad Dahlan, 2024)
This research focuses on the Adult Silent Period in Second Language Acquisition (SLA), examining ways to combat proficiency silences from the perspective of advanced speaking bilinguals who reflected on how they ‘broke their silence’. The paper argues that proficiency-oriented silence in language-learning adults can improve through repetitive speaking practice in ELICOS. The pedagogical approach needs to fit the purpose of improving proficiency. The data collection included three stages, a survey with 148 advanced level bilinguals, analyses of a publicly available YouTube video of a pre-intermediate class, and teacher interviews. Findings from bilingual students’ self-reports on their early experiences in learning the English language in pre-intermediate classes showed that when the silent period in adult language learning is ignored by teachers due to their silencing monological teaching, language production is unnecessarily delayed. These students argued that their teachers emphasized the study of form above opportunities for meaning-making. The study suggests that acknowledging and addressing the silent period in adult language learners is crucial for facilitating language proficiency. Effective pedagogical strategies that prioritize repetitive speaking practice and meaningful interaction over a rigid focus on grammatical form can accelerate language production in adult learners. The findings imply that language educators in ELICOS programs should adapt their teaching methods to incorporate more communicative practices, thereby reducing the silent period and enhancing learners' speaking proficiency. The conclusion drawn from this research is that a balanced approach, which combines form-focused instruction with ample opportunities for meaning-making, can significantly improve the language acquisition process for adult learners.